Middle cerebral artery peak systolic velocity monitoring of fetal anemia during chemotherapy in pregnancy - Babkova, Anna; Rob, Lukas; Kubecova, Martina; Hruda, Martin; Halaska, Michael J (Acta obstetricia et gynecologica Scandinavica, 2024)
INTRODUCTION: Chemotherapy during pregnancy can increase the risk of fetal anemia. Severe fetal anemia can lead to the development of hydrops fetalis and potentially fetal demise. Hence, it is imperative to implement consistent monitoring methods in the context of chemotherapy treatment. This study aimed to diagnose and monitor fetal anemia using middle cerebral artery peak systolic velocity (MCA-PSV) as a diagnostic tool during chemotherapy in pregnant women. MATERIAL AND METHODS: The study employed a prospective analysis involving a case series of 15 patients diagnosed with cancer during pregnancy and subsequently underwent chemotherapy. MCA-PSV was used to identify fetal anemia. The patients were scheduled for ultrasound examinations of the MCA-PSV. The first examination was performed on the same day as the administration of chemotherapy, while the second occurred on the 10th day after chemotherapy. The measurement technique used in the study was based on the methodology proposed by Mari and Barr. The multiples of the median were calculated using the calculators provided by Medicina Fetal Barcelona. Based on these values anemia severity was determined. When moderate or severe anemia was identified, chemotherapy was individually modified. Additionally, a blood count analysis was conducted immediately after the delivery of the newborn. RESULTS: Five patients were diagnosed with fetal or newborn anemia. With MCA-PSV, we identified moderate fetal anemia in two patients and severe fetal anemia in one. The complete blood count testing of newborns revealed mild anemia in three patients. One case was unrelated to chemotherapy-induced anemia. During treatment, fetal anemia did not corelate with maternal anemia. CONCLUSIONS: In four cases of anemia the combination of cisplatin and iphosphamide was used as a chemotherapy agent. No anemia was observed in other drug combinations. Our findings suggest that MCA-PSV is a reliable method for identifying anemia and should be included in the treatment protocol for chemotherapy-induced fetal anemia.
Keywords: Ultrasonography, Prenatal; novorozenec; Infant, Newborn; Pregnancy; Humans; nemoci plodu; Blood Flow Velocity; Female; Antineoplastic Agents; ultrasonografie prenatální; Middle Cerebral Artery; Fetal Diseases; fetal anemia; lidé; ženské pohlaví; pregnancy; arteria cerebri media; rychlost toku krve; middle cerebral artery peak systolic velocity; těhotenství; Anemia; anemie; protinádorové látky; chemotherapy